The Influence of Leadership Innovation and Collaboration on the Performance of West Sumatra Provincial Health Service ASN - Afando Ekardo; Cashtry Meher; Ahyar Wahyudi (Formosa Journal of Science and Technology, 2024)
The performance of civil servants is needed in a government agency to improve performance. Therefore, to make it happen, skilled and reliable human resources are needed in their fields. Innovation in the field of public services is needed for the creation of comfortable public services. Collaborative leadership is needed to cope with rapid change. The purpose of this study is to determine the Influence of Innovation and Leadership Collaboration on the Performance of ASN of the West Sumatra Provincial Health Office. The qualitative research method uses a descriptive approach, where the data collected is in the form of interview manuscripts, field notes, and other official documents. The results of innovation show that the form of public service ""Go to Heaven" and "Rasa Heaven" are two creative innovations applied in public services in the health sector that have received appreciation from the government and the community.  The conclusion and implementation of the research results that the performance of civil servants can be improved through innovations born by leaders and in collaboration with their staff as well as collaboration with leaders in the City Regency area in replicating these innovations, so as to realize public services that satisfy the community and can reduce the number of pain in the community.